Examining the Impact of School Principals’ Leadership and Family–Teacher Synergy on Elementary Students’ Prosocial Behavior - Gusmin, Eka Milasari; Zakso, Amrazi; Sanulita, Henny (Jurnal Paedagogy, 2026)
This study aims to examine the influence of principal leadership and family–teacher synergy on the prosocial behavior of elementary school students at SD Negeri 05 Pontianak Selatan. A quantitative survey approach was employed, with data collected from 88 students in Grades IV, V, and VI using validated questionnaires. The data were analyzed using descriptive statistics and inferential analysis, including percentage analysis to categorize variables and regression analysis to examine the relationships among variables. The results indicate that students’ prosocial behavior was generally at a positive level, with most students categorized as high, although variations were observed across dimensions. Helping and sharing showed the highest levels, while empathy and environmental care still require improvement. Principal leadership demonstrated strong effectiveness, particularly in community empowerment and instructional leadership. Similarly, family–teacher synergy showed high effectiveness, especially in learning support and character-building collaboration, although communication and value consistency remain areas for improvement. The findings suggest that concrete prosocial behaviors are more easily developed through habituation, whereas more complex behaviors require structured and continuous interventions. In conclusion, this study highlights the importance of strengthening transformational leadership and enhancing collaboration between schools and families to create a supportive educational ecosystem. It also underscores the need for differentiated character education programs and more intensive communication strategies to optimize students’ prosocial development.